Análise do planejamento urbano de Calçoene de 2001 a 2015 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The Urban planning of Calçoene was analyzed in the period 2001-2015, and focused on the city council headquarters. The documents that supported the research were raising the potential, talent and comparative advantages of the municipality and the plan arising from this, which had an emergency. It is an applied research, with the exploratory nature of the aims, qualitative and quantitative how to approach, using the dialectical method. We started from the hypothesis that the small municipalities in the State of Amapa, as Calçoene, has no effectiveness urban planning that guides, in fact, the actions carried out in the city, although they happen to answer the local, punctual and shortsighted demands without being provided by a macroplan, where there is continuity of actions fulfilling goals short, medium and long term. The results show that there was the fulfillment of actions suggested by the plan, guided actions, and also shares with no immediate results and timely character were neither suggested and / or guided by the plan. Actions with favorable status, in the proposed period, when categorized by large areas, showed that the infrastructure category was the one with the highest rate, in total 20, representing 33.90%, priority already highlighted in the emergency plan. Thus, it can be said that there was a contradiction of the hypothesis
Keywords: Planejamento urbano; Espaço urbano; Calçoene (AP); CNPQ::CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; DESENVOLVIMENTO E PLANEJAMENTO SOCIOECONÔMICO; MEIO AMBIENTE, CULTURA E DESENVOLVIMENTO REGIONAL